THE EFFECT OF CORPORATE GOVERNANCE MECHANISM ON EARNINGS MANAGEMENT PRACTICE (Case Study on Indonesia Manufacturing Industry) - YULIUS KURNIA SUSANTO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
The purpose of the research is to get empirical evidence about institutional ownership, management ownership, directors’ size, audit committee, independent commissioner, leverage, profitability, firm size, auditor’s independency and auditor’s reputability on earnings management practice. This research used 53 manufacturing companies listed in Indonesia Stock Exchange and the data were collected through purposive sampling method during the research period 2009 until 2011. The result of the research showed that audit committee, independent commissioner and debt to equity ratio had influence on earnings management practice. The results of this study indicate that the audit committee and independent commissioner overseeing management in reporting of company performance through financial statements. In addition, companies that source of funding more debt than equity is more likely to make an earnings management.